Role of the sodium channel SCN9A in genetic epilepsy with febrile seizures plus and Dravet syndrome. Issue 9 (29th July 2013) - Mulley, John C.; Hodgson, Bree; McMahon, Jacinta M.; Iona, Xenia; Bellows, Susannah; Mullen, Saul A; Farrell, Kevin; Mackay, Mark; Sadleir, Lynette; Bleasel, Andrew; Gill, Deepak; Webster, Richard; et al.
Summary Mutations of the SCN1A subunit of the sodium channel is a cause of genetic epilepsy with febrile seizures plus (GEFS+) in multiplex families and accounts for 70–80% of Dravet syndrome (DS). DS cases without SCN1A mutation inherited have predicted SCN9A susceptibility variants, which may contribute to complex inheritance for these unexplained cases of DS. Compared with controls, DS cases were significantly enriched for rare SCN9A genetic variants. None of the multiplex febrile seizure or GEFS+ families could be explained by highly penetrant SCN9A mutations.